Dynamic Knee Joint Line Orientation Is Not Predictive of Tibio-Femoral Load Distribution During Walking - Trepczynski, Adam; Moewis, Philippe; Damm, Philipp; Schütz, Pascal; Dymke, Jörn; Hommel, Hagen; Taylor, William R.; Duda, Georg N. (Frontiers in Bioengineering and Biotechnology, 2021)
Some approaches in total knee arthroplasty aim for an oblique joint line to achieve an even medio-lateral load distribution across the condyles during the stance phase of gait. While there is much focus on the angulation of the joint line in static frontal radiographs, precise knowledge of the associated dynamic joint line orientation and the internal joint loading is limited. The aim of this study was to analyze how static alignment in frontal radiographs relates to dynamic alignment and load distribution, based on direct measurements of the internal joint loading and kinematics. A unique and novel combination of telemetrically measured in vivo knee joint loading and simultaneous internal joint kinematics derived from mobile fluoroscopy (“CAMS-Knee dataset”) was employed to access the dynamic alignment and internal joint loading in 6 TKA patients during level walking. Static alignment was measured in standard frontal postoperative radiographs while external adduction moments were computed based on ground reaction forces. Both static and dynamic parameters were analyzed to identify correlations using linear and non-linear regression. At peak loading during gait, the joint line was tilted laterally by 4° to 7° compared to the static joint line in most patients. This dynamic joint line tilt did not show a strong correlation with the medial force (R2: 0.17) or with the mediolateral force distribution (pseudo R2: 0.19). However, the external adduction moment showed a strong correlation with the medial force (R2: 0.85) and with the mediolateral force distribution (pseudo R2: 0.78). Alignment measured in static radiographs has only limited predictive power for dynamic kinematics and loading, and even the dynamic orientation of the joint line is not an important factor for the medio-lateral knee load distribution. Preventive and rehabilitative measures should focus on the external knee adduction moment based on the vertical and horizontal components of the ground reaction forces.